2019
DOI: 10.1038/s41598-019-51599-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined CT radiomics of primary tumor and metastatic lymph nodes improves prediction of loco-regional control in head and neck cancer

Abstract: Loco-regional control (LRC) is a major clinical endpoint after definitive radiochemotherapy (RCT) of head and neck cancer (HNC). Radiomics has been shown a promising biomarker in cancer research, however closer related to primary tumor control than composite endpoints. Radiomics studies often focus on the analysis of primary tumor (PT). We hypothesize that the combination of PT and lymph nodes (LN) radiomics better predicts LRC in HNC treated with RCT. Radiomics analysis was performed in CT images of 128 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 24 publications
1
33
3
2
Order By: Relevance
“…Even though usually radiomic models obtained from multiparametric MRI are the ones that perform better [ 13 ], this is not the first time that monomodal radiomic models result to be the best [ 16 ]. The results are also partially in contrast with [ 17 ], in which the addition of lymph node features significantly improved the results, but this may be explained taking into account the differences in terms of type of pathology (NPC vs. generic head and neck cancer), the definition of the lymphnodal ROI (all the nodal masses vs. the largest lymph node), the different imaging technique (computed tomography vs. MRI).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Even though usually radiomic models obtained from multiparametric MRI are the ones that perform better [ 13 ], this is not the first time that monomodal radiomic models result to be the best [ 16 ]. The results are also partially in contrast with [ 17 ], in which the addition of lymph node features significantly improved the results, but this may be explained taking into account the differences in terms of type of pathology (NPC vs. generic head and neck cancer), the definition of the lymphnodal ROI (all the nodal masses vs. the largest lymph node), the different imaging technique (computed tomography vs. MRI).…”
Section: Discussioncontrasting
confidence: 75%
“…Only N+ patients were considered for the analysis since it has been shown in previous studies related to head and neck cancer that the addition of radiomic features from the lymphnodal ROI provides a better prognostic ability than radiomics from the main tumor alone [ 17 , 35 ]. Metastatic lymph node involvement was defined according to Ho et al [ 36 ]: criteria included, namely, central necrosis, extra capsular spread, shortest diameter of cervical or medial retropharyngeal lymph nodes >1 cm and >5 mm for lateral retropharyngeal lymph node(s).…”
Section: Methodsmentioning
confidence: 99%
“…However, in our study the AUC value determined for the validation cohort was still 0.59 but the significance of the CT radiomics model to stratify patient risk groups could not be confirmed in this cohort in contrast to other published studies [37][38][39]. In one study by Bogowicz et al [36] a CT radiomics model based on the primary tumour volume could not be validated in contrast to a model, which was applied to primary tumour and lymph node volumes. According to these findings, the fact that in our study CT radiomics was assessed for the primary tumour only whereas loco-regional failure was used as a prediction variable might be a further limitation.…”
Section: Discussioncontrasting
confidence: 92%
“…Several recent studies published CT radiomics models for predicting local control or overall survival in HNC patients following CRT [36] , [37] , [38] , [39] . Similar to our findings, those studies identified features related to CT value homogeneity as most relevant for outcome prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics has attracted increased attention in recent years, and several studies show that radiomics can be of benefit in terms of prognosis and diagnosis of multiple diseases, [21][22][23]. These studies have shown that radiomics features show great potential to serve as surrogate imaging markers for tissue biopsies [40] and reliably predict outcome [41][42][43][44] and drug response [45,46]. Currently, there are different approaches for the evaluation of HRCT, namely (1) visual analysis, (2) semiquantitative analysis, and (3) quantitative analysis or automated approaches using artificial intelligence.…”
Section: Discussionmentioning
confidence: 99%